Impact of COVID-19 Pandemic on Consumer Buying Behavior of Organic Products in Surkhet Valley, Nepal (The International Research Journal of Management Science, 2024)
Purpose: This study investigates the impact of the COVID-19 pandemic on consumer buying behavior of organic products in Surkhet Valley, Nepal. It explores how various factors, including the pandemic phase, perceived health risk, income loss, governmental regulations, and media influence, have shaped purchasing patterns during the pandemic.Methodology: A survey was conducted among 400 organic product consumers from Surkhet Valley, using a convenience sampling technique. Data collection took place between June and July 2024 and analysis was performed using Smart PLS software to test relationships and hypotheses. Cronbach’s Alpha was employed to assess validity and reliability.Findings: Results show that pandemic phases, perceived health risks, and media influence significantly affected consumer behavior. Economic hardship and government regulations also played roles in limiting access to organic products. Consumers perceived organic products as safer during early pandemic phases but reverted to previous buying habits over time.Limitations/ Implications: The study is limited to Surkhet Valley and convenience sampling, which may limit generalizability. Nevertheless, these insights are valuable for businesses and policymakers seeking to adapt strategies for the organic product market in post-pandemic settings, promoting resilience and sustainability.